Fluid Inclusions in Surface‐temperature Halite: Sample Preparation and Application. (5th September 2018) - WANG, Mingquan; ZHAO, Yanjun; LI, Wenxia; LIU, Chenglin
Abstract : Abstract: Paleo‐temperature and paleo‐environment can be interpreted from measuring homogenization temperatures of fluid inclusions within halite. In order to conduct such measurements, vapor bubbles within low‐temperature fluid inclusion often need to be created through cooling process by using cooling stage or freezer. Proper cooling is critical for interpreting measured temperature data. We tested two common cooling methods, using heating/freezing stage and freezer, for studying fluid inclusions in halite precipitated in laboratory at conrtolled temperature of 25°C. While using the heating/freezing stage, halite samples were kept at –18°C for 40–50 min; whereas for freezer, samples were stored at –18°C for 1, 10, 20 and 40 days, respectively. By comparing the homogenization temperatures of the two cooling processes, we explored the detailed experimental processes and developed an optimal cooling nucleation procedure for homogenization temperature analyses of fluid inclusions within surface‐temperature halite. The results show that the maximum homogenization temperatures from both methods approximate the actual brine temperature of 25°C. However, extended refrigeration time has noticeable influence on the results. The refrigeration time of the experiment can be shortened to meet requirements.